A comparison of mtDNA and Y chromosome diversity in Malay populations - Bekaert, B.; Zainuddin, Zafarina; Hadi, S.; Goodwin, W. (Elsevier, 2006)
The mtDNA and Y chromosomes of the Malay population of peninsular Malaysia show high levels of diversity. Both the Malay and the indigenous Orang Asli populations showed a similar level of divergence between the different Y chromosome haplotypes